Severe theophylline poisoning treated with continuous venovenous hemodialysis in a child - Yaman, Ayhan; Kendirli, Tanıl; Ödek, Çağlar; Azapağası, Ebru; Erkol, Hatice; Pişkin, İbrahim Etem; Teber-Tıraş, Serap; Yalçınkaya, Fatoş (The Turkish Journal of Pediatrics, 2016)
Theophylline poisoning generally occurs due to acute high dose intake as well as chronic intake of the medication. Toxicity symptoms can be seen with a plasma concentration of theophylline over 20 μg/ml. The consequences of theophylline toxicity include metabolic disturbances (hypokalemia, hyperglycemia, and metabolic acidosis), nausea, vomiting, and in severe cases seizures, cardiac arrhythmias, and death. Theophylline poisoning in children is rarely described in the literature. A 3-year-old girl was referred from another hospital to our pediatric intensive care unit (PICU) due to prolonged refractory status epilepticus and respiratory failure linked with severe theophylline poisoning. The patient was admitted to our PICU 24 hours after the patient took theophylline. The referring center could not measure the serum theophylline level. The patient's first serum theophylline level that was checked at admission was 54 μg/ml. We started continuous venovenous hemodialysis (CVVHD) 3 hours after PICU admission and the patient's theophylline level successfully decreased within 9 hours. The patient was discharged at the 40th day of admission from our hospital with severe neurological disability. In conclusion, severe theophylline poisoning may be seen in children. We must consider CVVHD in critically ill children with severe theophylline poisoning.
Keywords: children; continuous venovenous hemodialysis; pediatric intensive care unit; seizures; theophylline poisoning